2009
DOI: 10.1111/j.1551-2916.2008.02673.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Lamellae Spacing During Freeze Casting of Ceramics Using Double‐Side Cooling as a Novel Processing Route

Abstract: A processing route for freeze-casting of particle suspensions is presented, where the microstructure development during the solidification process can be controlled precisely. For this purpose, the single-side cooling and double-side cooling methods are compared. A procedure will be shown to control the freezing process using the double-side cooling method. Our approach was to determine the freezing conditions in order to forecast the freezing velocity and to carry out an advanced directional solidification se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 18 publications
4
122
1
Order By: Relevance
“…interconnectivity and size) in the final material depend on its initial position within the mould. 173,174 Thus, not only the direction of the resulting pores but also their characteristics can be tailored by the design of the cooling part (or parts). 173 Though, the freedom of design is to some extent limited by the necessity of using a mould (to carry the liquid) with the accompanying requirement of removing the mould after freezing.…”
Section: Zeolitic Monoliths Via Freeze Castingmentioning
confidence: 99%
“…interconnectivity and size) in the final material depend on its initial position within the mould. 173,174 Thus, not only the direction of the resulting pores but also their characteristics can be tailored by the design of the cooling part (or parts). 173 Though, the freedom of design is to some extent limited by the necessity of using a mould (to carry the liquid) with the accompanying requirement of removing the mould after freezing.…”
Section: Zeolitic Monoliths Via Freeze Castingmentioning
confidence: 99%
“…Deville et al 2006a;Fu et al 2008a;Pekor et al 2008). The advantage of two-sided freeze-casting systems, in which the bottom and top of the mould are closed by copper plates whose temperature can be varied independently, is that the temperature gradient and freezing-front velocity within the sample can be better controlled (Deville et al 2006a,c;Waschkies et al 2009). In both systems, Figure 2.…”
Section: The Freezing Processmentioning
confidence: 99%
“…In most freeze-casting systems, the applied cooling rate is measured at the cold-finger-sample interface, but not the velocity of the freezing front during processing itself. However, in systems that are equipped with a thermocouple array embedded in the mould, the freezing-front velocity can be measured directly and the cold-finger cooling rate adjusted to achieve a desired value (Waschkies et al 2009). Once the temperature of the cold finger is lower than the solidification temperature of the slurry, a freezing front, defined as the interface between the solid and the liquid phases, is formed and starts to travel through the sample.…”
Section: The Freezing Processmentioning
confidence: 99%
“…Munch et al 71 showed that patterning the freezing surface can manipulate the long-range ordering of ice lamellae by controlling the initial direction of nucleation. Deville et al 67 and Waschkies et al 83 used double-sided cooling to more precisely control the temperature gradient. Moon et al, 84 Macchetta et al, 49 and Koh et al 85 demonstrated the concept of radial cooling to construct porous ceramics with radial channel alignment (Fig.…”
Section: Microstructural Controlmentioning
confidence: 99%